Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1993
DOI: 10.1073/pnas.90.11.5021
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of metastasis by inhibition of the urokinase receptor.

Abstract: The plasminogen activator urokinase (u-PA) mediates proteolysis by a variety of human tumor cells. Competitive displacement ofu-PA from cellular binding sites results in decreased proteolysis in vitro, suggesting that the cell surface is the preferred site for u-PA-mediated protein degradation. We studied the effect of u-PA receptor blockade on the metastatic capacity of human PC3 prostate carcinoma cells, using transfectants which expressed chloramphenicol acetyl-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
202
4

Year Published

1996
1996
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 343 publications
(220 citation statements)
references
References 14 publications
11
202
4
Order By: Relevance
“…As a result, a much greater fraction of the total energy is deposited in cells with alpha and very few nuclear hits are required to kill a cell. The expression of uPA/uPAR was found on a high percentage of human PC3 prostate cancer line (Crowley et al, 1993;Festuccia et al, 1998). Using immunocytochemistry and flow cytometry, we confirmed that uPA/uPAR was expressed on the surface of viable PC3 cells.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, a much greater fraction of the total energy is deposited in cells with alpha and very few nuclear hits are required to kill a cell. The expression of uPA/uPAR was found on a high percentage of human PC3 prostate cancer line (Crowley et al, 1993;Festuccia et al, 1998). Using immunocytochemistry and flow cytometry, we confirmed that uPA/uPAR was expressed on the surface of viable PC3 cells.…”
Section: Discussionmentioning
confidence: 99%
“…For example, intraperitoneal bolus injections of a human ATF-based antagonist has been shown to inhibit lung metastases of human tumor cells grown in athymic mice, with no significant effect on primary tumor growth. 9 In another study, intraperitoneal injections of peptides from murine ATF inhibited both primary tumor growth and dissemination. 10 Disruption of cell surface uPA/uPAR also inhibited bFGF-or VEGFinduced angiogenesis in an artificial bFGF-enriched extracellular matrix model.…”
Section: Introductionmentioning
confidence: 96%
“…Among them, the amino-terminal fragment of urokinase (ATF) is of particular interest because it can also exert a direct effect on the tumor cells and inhibit metastasis in experimental models. [9][10][11] Urokinase and its high affinity receptor, a GPI-anchored membrane protein (CD87), are believed to be critical elements in tumor biology because they control cell motility, tissue remodeling and the bioavailability of angiogenic factors. For example, uPA/uPAR complex formation at the cell surface is required for efficient activation of plasmin, a wide range protease that can degrade components of the basement membrane and the extracellular matrix (eg vitronectin, laminin, fibronectin), a prerequisite for tumor cell invasion.…”
Section: Introductionmentioning
confidence: 99%
“…UPAR and a5b1 induce EGFindependent but focal adhesion kinase-dependent EGF-R activation, generating high extracellular signalregulated protein kinase (ERK) and low p38 activity, conditions necessary for the growth of cancer cells in vivo (Aguirre-Ghiso et al, 1999, 2003Liu et al, 2002). Second, uPA and uPAR antagonists prevent not only invasiveness and metastasis dissemination but also tumor growth (Crowley et al, 1993;Min et al, 1996;Lakka et al, 2001;Ploug et al, 2001). Finally, a genetic screen in Ink4a À/À mice identified uPAR as a potential cooperating oncogene (Lund et al, 2002).…”
Section: Introductionmentioning
confidence: 99%